Postural sway during single-legged standing is dependent on the preceding and subsequent action and supports the stability and mobility trade-off hypothesis in classical dancers - Bacik, B.; Sobota, G.; Fredyk, A.; Juras, G.; Slomka, K. J. (Sports Biomechanics, 2021)
The details on how the position of balance examination is achieved (preceding movement) and what is happening after (subsequent movement) is scarce. We hypothesised that the postural sway in quiet standing can differ due to demanded stability or mobility associated with the preceding and subsequent action. The body sway will be lower with high stability demand task than a condition with high mobility task. Thirteen female ballet students were examined (aged 15.1 ± 0.95 years). Participants were examined in the single-legged standing position as a part of gait initiation (G-I, high mobility) and termination (G-T, high stability) task with the use of force plate. The following Centre of Pressure (COP) variables were analysed: range and standard deviation of COP position, mean COP velocity for AP (anterio-posterior) and ML (medio-lateral) planes. The results showed that for ML plane, body sway was larger for G-I than G-T task. The lowest values of all variables in AP plane (except the COP range) were for G-T task. This difference, confirm our hypothesis, where this difference is not caused by the skills of the participants, but due to the measuring procedure and motor behaviour before and after achieving the measurement position. Our conclusion is limited to the specific posture and homogenous participants.